Relative age effect, biological maturation, and coaches` efficacy expectations in young male soccer players - Peña-González, I.; Fernández-Fernández, J.; Moya-Ramón, M.; Cervelló, E. (Research Quarterly for Exercise and Sport, 2018)
Purpose: The talent identification and selection process in young male soccer players is mainly focused on anthropometrics and physical performance, but social factors are also considered in this process. The purpose of this study was to test the existence of the relative age effect and its possible influence on anthropometrics and physical performance and to analyze coaches` efficacy expectations. Method: Data for 564 young male soccer players (Mage = 13.7 ± 1.5 years; Mweight = 53.7 ± 11.6 kg; Mheight = 160.2 ± 11.6 cm) included their birth quartile, maturity status, anthropometrics, a physical test battery, and coaches` efficacy expectations. Results: Early-born players were overrepresented (p < .05). Early-born players were not statistically taller, heavier, or better at physical performance (p > .05) when maturation and chronological age were controlled as confounding factors. However, coaches expected more from early-born players (p < .05), and the inferential analysis showed likely to very likely worthwhile differences between the coaches` expectations for players born in the first quartile of the year and those born in the fourth quartile of the year. Conclusions: Anthropometrical and physical performance variables were not affected by birth quartile, and coaches` efficacy expectations were related to the relative age effect.